Estimation of Nitrogen Loading to Surface Water from Agriculture Based Area and Its Application for Water Pollution Mitigation: 10.32526/ennrj/19/2020239 - Thitanuwat, Bussarakam; Wongsoonthornchai, Manaporn (Environment and Natural Resources Journal, 2021)
Eutrophication of surface water is a globally widespread environmental problem. Similarly, in Thailand, the Nakhon Nayok River (NNR), located in an agriculture-based area, has been markedly affected by eutrophication problems. However, there are limited studies on significant nitrogen (N) sources during agricultural activities in the area. Therefore, this study examined the major sources and key flows of N loading to the surface water by applying material flow analysis (MFA) to the relevant seven subsystems in 2018. The results showed that aquaculture and rice cultivation were the main sources of nitrogen inputs and outputs. Both considerably contributed to the nitrogen loading to the surface water, yet nitrogen released from the aquaculture was five times higher than the rice cultivation. The nitrogen flux found in the study area was 0.11 kg/ha. Accordingly, creating wetlands for aquaculture wastewater treatment that could potentially remove nitrogen by 12% was recommended.